Cutis MarmorataTelangectásica Congénita - Rubi Rodas, Perla Esmeralda; Caballero Castro, Héctor Rubén (Acta Pediátrica Hondureña, 2015)
Acta Pediátrica Hondureña, Vol. 4, No. 2 / Octubre 2013 a Marzo 2014: 312